UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK SMK MELALUI STRATEGI PEMBELAJARAN SELF REGULATED LEARNING - Nurul Septiani Ayu Purwanti (UJMES (Uninus Journal of Mathematics Education and Science), 2017)
This research is based on the students’ self regulation and mathematics learning result. One of alternative learning that can be applied to improve mathematics learning result of students is by using learning strategies of Self Regulated Learning. This study aims to determine the increase of learning outcomes of students with learning strategies Self-Regulated Learning and opinions of students referred to instructional strategies of Self Regulated Learning. The method used in this research is the Classroom Action Research (CAR), which refers to measure with a cycle of planning, action, observation, and reflection. The subjects were all students of class XI at a private vocational school in Bandung. The data collection instruments used consisted of pieces of observation, achievement test, questionnaire, and journals. In this research, the qualitative data obtained from observations, and daily journals. While quantitative data obtained from the questionnaires and tests of self-regulation learning outcomes of students. Data analysis of the observation sheet is by using the percentage of the daily journal while the questionnaire analysed by using Likert sale and achievement test using the calculation of the average value in one class. Based on observations analysis it was concludded that increased activity educators, daily journal analysis showed that learners have a positive opinion towards learning by using learning strategies of Self Regulated Learning. Meanwhile, the analysis of the achievement test increased after the implementation of learning strategies Self Regulated Learning.